Сhallenging Questions of Development and Application of DNA Banks for the Purposes of Criminology and Related Disciplines - M. V. Sprindzuk; L. P. Titov; A. P. Konchits (Цифровая трансформация)
Review article presents essential information on DNA databases, forensic genomics for human identification and suspect characteristics. Author reports the essential information on the topic of forensic DNA databases and data processing. DNA databases are important tools for the improvement of performance of the security organizations and services with a final goal of national security enhancement.